Combination of sequence‐defined oligoaminoamides with transferrin‐polycation conjugates for receptor‐targeted gene delivery. (9th August 2015) - Zhang, Wei; Rödl, Wolfgang; He, Dongsheng; Döblinger, Markus; Lächelt, Ulrich; Wagner, Ernst
Abstract Background Transferrin receptor (TfR), over‐expressed on a majority of malignant cells, has been widely studied as a target for drug, protein and gene delivery. Both stable nucleic acid compact ability and efficient cytosol gene release capability are essential for the success of gene delivery. Methods In the present study, a novel nonviral TfR‐targeted gene delivery system was developed based on sequence‐defined cationic oligoaminoamide oligomers with endolysosomal buffer capacity and DNA binding transferrin (Tf) polycation conjugates. Results Gene transfer activities were significantly increased in a series of TfR over‐expressing human tumour cell lines (K562, DU145 and KB) with mixed ternary polyplexes containing Tf‐conjugates and 3‐arm (386 and 689) or 4‐arm (577, 579 and 607) sequence‐defined oligomers. Especially polyplexes containing a histidine‐rich 4‐arm oligomer (607) and Tf‐PEG‐PEI achieved a 100‐fold increase in gene expression compared to previously established formulations. Tf competition experiments indicate enhanced polyplex internalization via TfR as prerequisite for the high transfection activity. The additional histidines in the oligoaminoamide oligomer structure are required for more effective endolysosomal escape of the gene delivery vehicle. Polyplexes formed by first mixing pDNA with the oligomer as a cationic core, followed by the addition of the Tf‐polycation conjugate for presentation at the exterior nanoparticles, exhibited the highest transfection activity. Conclusions Utilizing the synergistic effects of Tf for receptor targeting and oligomer for packaging and endolysosomal escape, an efficient gene delivery carrier was developed. The mixed polyplex containing Tf‐polycation conjugates and histidinylated 4‐arm oligomer with succinoyl tetraethylene pentamine or glutaroyltriethylene tetramine building blocks exhibited the highest gene transfection efficiency in TfR over‐expressing human tumour cell lines. Copyright © 2015 John Wiley & Sons, Ltd.